Senecio angulatus L.f. (Asteraceae) a new addition to the Moroccan alien flora - Khamar, Hamid; El Bakhouch, Hasna (UMA Editorial, 2024)
Senecio angulatus L.f. (Asteraceae), native to South Africa, is reported here as a new non-native plant to the vascular flora of Morocco for the first time. The species’ diagnostic morphological characters, photographic illustration, data on geographic distribution and ecology, and probable invasion pathway are provided and commented.

Senecio angulatus L.f. (Asteraceae), especie nativa del sur de África, es citada por primera vez como especie alóctona de la flora vascular de Marruecos. Se muestran y comentan caracteres morfológicos diagnósticos de especie, fotografías, datos de distribución geográfica, ecológicos y de probable vía de invasión.
Keywords: Asteráceas - Marruecos; Flora - Introducción; Flora exótica; Corología; Nueva cita; Marruecos